HUSK CHARCOAL MAKING TRAINING WITH CARBONIZATION MACHINE DURING COVID-19 TO IMPROVE COMMUNITY WELFARE IN SUKOHARJO REGENCY - Sriyanto Sriyanto; Rahmad Rahmad; Totok Wartiono; Suhartoyo Suhartoyo (STKIP PGRI SITUBONDO, 2022)
The COVID-19 pandemic has changed all social activities in the community. The community is required to comply with health protocols by maintaining a distance between one person and others (Social distancing) and even a closure of activities that occur in an area (Lockdown) resulting in all activities being completely stopped, whether school, office or business activities in the community. Community activities that have changed due to saturation have made people have the idea of ​​growing ornamental plants. This activity resulted in the demand for growing media to increase, resulting in the supply of plant traders becoming scarce. Pak Harno's Flower Kiosk whose address is at Jl. Raya Jlopo, Hamlet III, Gedangan, Kec. Grogol, Sukoharjo Regency, Central Java is also the impact of the scarcity of plant media in the form of roasted husks. On the basis of this problem Community Service Activities held activities in the form of making appropriate technology tools, namely roasted rice husks which will be donated to partners. donating only tools but also providing training supplies for making roasted husks to partners, training in packaging manufacture and product packaging. From this activity the activity implementation team produces outputs in the form of media publications and Community Service journal